Convergence on iterative learning control of Hilfer fractional impulsive evolution equations. Issue 3 (10th July 2022) - Raghavan, Divya; Nagarajan, Sukavanam
Abstract: In this paper, impulsive fractional differential equations with Hilfer fractional derivatives of order 0 < μ < 1 0<μ <1 and type 0 ≤ ν ≤ 1 0ν 1 is considered. Convergence analysis of P P ‐type and P I μ PI^μ ‐type open‐loop iterative learning scheme is studied in the sense of λ λ ‐norm. Examples are provided to explain the theory developed.